Effect of Topical Laportea Decumana Leaves Extract on Labor Pain and Cortisol Level in the First Active Phase of Inpartu Condition - Sisma HL (Journal of Global Pharma Technology, 2020)
This research aims to obtain the effect of L. Decumana extract toward labor pain and cortisol level in the first active phase of inpartu condition. This research used True Experimental with pre post test control group on the first active phase in inpartu condition. This research was combining pharmacology and non-pharmacology method. In choosing the research’s subject, consecutive sampling and randomization were applied to divide the subject into four groups. To measure the pain level, Visual Analog Scale (VAS), and saliva liquid was applied to measure the level of cortisol. The smallest average of pain level before the treatment was KS+V group (6,40) and the highest was LD+KS group (7,70). After the treatment, the smallest level was in LD+KS (5,60) group and the highest is in the SP+V group (7,00). It meant that there was reduction in the pain level before and after treatment. L. Decumana as the medical medicine can be used as reducing the first active phase of labor pain in inpartu condition. However, the further research is needed to prove the effect of biomarker L. Decumana to initiate labor.